g-NK cells from umbilical cord blood are phenotypically and functionally different than g-NK cells from peripheral blood - Fei Gao; Mauricio Campos Mora; Michael Constantinides; Loïs Coenon; Caroline Multrier; Loïc Vaillant; Tianxiang Zhang; Martin Villalba (OncoImmunology)
FcRγ-deficient natural killer (NK) cells, designated as g-NK cells, exhibit enhanced antibody-dependent cellular cytotoxicity (ADCC) capacity and increased IFN-γ and TNF-α production, rendering them promising for antiviral and antitumor responses. g-NK cells from peripheral blood (PB) are often associated with prior human cytomegalovirus (HCMV) infection. However, the prevalence, phenotype, and function of g-NK cells in umbilical cord blood (UCB-g-NK) remain unclear. Here, we demonstrate significant phenotypical differences between UCB-g-NK and PB-g-NK cells. Unlike PB-g-NK cells, UCB-g-NK cells did not show heightened cytokine production upon CD16 engagement, in contrast to the conventional NK (c-NK) cell counterparts. Interestingly, following in vitro activation, UCB-g-NK cells also exhibited elevated levels of IFN-γ production, particularly when co-cultured with HCMV and plasma from g-NK+ adults. Furthermore, g-NK+ plasma from PB even facilitated the in vitro expansion of UCB-g-NK cells. These findings underscore the phenotypic and functional heterogeneity of g-NK cells based on their origin and demonstrate that components within g-NK+ plasma may directly contribute to the acquisition of an adult phenotype by the “immature” UCB-g-NK cells.